Sildenafil dosed concomitantly with bosentan for adult pulmonary arterial hypertension in a randomized controlled trial - Vizza, Carmine Dario; Jansa, Pavel; Teal, Simon; Dombi, Theresa; Zhou, Duo (BMC cardiovascular disorders, 2017)
BACKGROUND: Few controlled clinical trials exist to support oral combination therapy in pulmonary arterial hypertension (PAH). METHODS: Patients with PAH (idiopathic [IPAH] or associated with connective tissue disease [APAH-CTD]) taking bosentan (62.5 or 125 mg twice daily at a stable dose for ≥3 months) were randomized (1:1) to sildenafil (20 mg, 3 times daily; n = 50) or placebo (n = 53). The primary endpoint was change from baseline in 6-min walk distance (6MWD) at week 12, assessed using analysis of covariance. Patients could continue in a 52-week extension study. An analysis of covariance main-effects model was used, which included categorical terms for treatment, baseline 6MWD (<325 m; ≥325 m), and baseline aetiology; sensitivity analyses were subsequently performed. RESULTS: In sildenafil versus placebo arms, week-12 6MWD increases were similar (least squares mean difference [sildenafil-placebo], -2.4 m [90% CI: -21.8 to 17.1 m]; P = 0.6); mean ± SD changes from baseline were 26.4 ± 45.7 versus 11.8 ± 57.4 m, respectively, in IPAH (65% of population) and -18.3 ± 82.0 versus 17.5 ± 59.1 m in APAH-CTD (35% of population). One-year survival was 96%; patients maintained modest 6MWD improvements. Changes in WHO functional class and Borg dyspnoea score and incidence of clinical worsening did not differ. Headache, diarrhoea, and flushing were more common with sildenafil. CONCLUSIONS: Sildenafil, in addition to stable (≥3 months) bosentan therapy, had no benefit over placebo for 12-week change from baseline in 6MWD. The influence of PAH aetiology warrants future study. TRIAL REGISTRATION: ClinicalTrials.gov NCT00323297 (registration date: May 5, 2006).
Keywords: antagonisté endotelinového receptoru; senioři; Walk Test; dvojitá slepá metoda; Treatment Outcome; sildenafil citrát; arteriální tlak; arteria pulmonalis; Double-Blind Method; tolerance zátěže; Time Factors; Sildenafil - Bosentan - pulmonary hypertension - randomized controlled trial -exercise test; výsledek terapie; Least-Squares Analysis; Drug Therapy, Combination; obnova funkce; Hypertension, Pulmonary; Middle Aged; mužské pohlaví; metoda nejmenších čtverců; Adult; sulfonamidy; Combination therapy; Bosentan; antihypertenziva; Pulmonary Artery; Antihypertensive Agents; kombinovaná farmakoterapie; ženské pohlaví; plicní hypertenze; test chůzí; Humans; Phosphodiesterase 5 Inhibitors; Recovery of Function; Sulfonamides; bosentan; vazodilatancia; Vasodilator Agents; časové faktory; lidé středního věku; Arterial Pressure; Sildenafil Citrate; dospělí; inhibitory fosfodiesterasy 5; Female; Aged; Exercise Tolerance; Endothelin Receptor Antagonists; lidé; Male